Emergence of teicoplanin-resistant coagulase-negative staphylococci. - Cercenado, E (1996)
Over a period of 5 years we have recovered 32 clinical isolates of coagulase-negative staphylococci (CoNS) exhibiting either decreased levels of susceptibility or true resistance to teicoplanin (MICs, 16 to 128 micrograms/ml); these isolates make up 0.55% of the total CoNS isolated by us. Twenty-nine of the strains were also methicillin resistant, and all were susceptible to vancomycin. Fourteen of the strains were Staphylococcus epidermidis, fourteen were Staphylococcus haemolyticus, and four were Staphylococcus hominis. In one case, a strain of S. haemolyticus was isolated with a vancomycin-resistant, teicoplanin-resistant Enterococcus faecalis strain. All strains were nosocomially acquired and were isolated from 17 different wards. Teicoplanin resistance occurred as a sporadic phenomenon, and none of the isolates were epidemiologically related. The isolates were from 30 patients, 13 of whom presented with true infections (43%). Five (38%) of the 13 patients with true infections had been previously treated with vancomycin. None of the infected patients were previously treated with teicoplanin. The in vivo development of resistance to teicoplanin among CoNS strains limits the therapy of infections by these microorganisms. There is a need for surveillance of nosocomial isolates of CoNS to determine resistance to glycopeptides.